Myšlení o válce na sklonku 20. století (Czech Journal of International Relations, 2000)
Michael Ignatieff: The Warrior´s Honor: Ethnic War and the Modem Conscience. Metropolitan Books,New York 1997, 207 stran, ISBN 0-8050-5518.Mary Kaldor: New and Old Wars: Organised Violence in a Global Era. Polity Press, Cambridge/Oxford1999, 192 stran, ISBN 0-7456-2067-1.